STATFREE - a software tool for biomechanics - Vieten, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Traditionally, a major part of the time invested into a study in biomechanics is devoted to the measuring process. The following data analysis is often statistics with its standard procedures as t-, F- and Chi²-testing. The strive for the analysis increases along with the expansion of theoretical background and/or model building. StatFree is a software for the post-measuring process. It performs statistical analysis, provides comprehensive graphic options and has a build-in programming utility to calculate the numeric efficiently and flexibly.